Concurrency Control in Distributed Database System - Singla, Anshu; Singha, Anjani Kumar; Gupta, Sudhir Kumar (IJRDO -Journal of Computer Science Engineering, 2016)
This paper reviews the coverage of concurrency control in Distributed Network. A distributed network becomesmore popular, the need for improvement in distributed database management systems becomes even more important. Themain challenges are identified as-: (1)Preserving the ACID property atomicity, consistency, isolation and durabilityproperty when concurrent transactions perform read and write operation; (2) provides recovery method when distributeddata is fail; (3)whatever method that is chosen they must provide feasible solutions with respect to performance.